DEVELOPMENT OF THE INFORMATION SYSTEM OF THE EDUCATIONAL CENTER ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The purpose of this study is to express the experiences, ideas, needs, and the use of information technology for the development of management information systems in a higher education institution. This study is a qualitative approach research using the case study method. The research data collection uses the techniques of observation, interview, and documentation study.